(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2025)
Bradykinin (or kinin) receptors (nomenclature as agreed by the NC-IUPHAR subcommittee on Bradykinin (kinin) Receptors [94]) are activated by the endogenous peptides bradykinin (BK), [des-Arg9]bradykinin, Lys-BK (kallidin), [des-Arg10]kallidin, [Phospho-Ser6]-Bradykinin, T-kinin (Ile-Ser-BK), [Hyp3]bradykinin and Lys-[Hyp3]-bradykinin. Variation in pharmacology and activity of B1 and B2 receptor antagonists at species orthologs has been documented. icatibant (Hoe140, Firazir) is approved in North America and Europe for the treatment of acute attacks of hereditary angioedema. Inhibition of bradykinin with icatibant in COVID-19 infection is under clinical evaluation, with trial NCT05407597.